Formação continuada dos profissionais de educação física das academias de ginástica de Cuiabá e Várzea Grande – MT - Mattos, Flávio Ramos de (2020)
It is necessary to understand that Continuing Education is not able to meet all the demands that the job market and its multiple realities impose on professionals, however, this does not diminish its importance of adherence, since initial formation is not enough for the professional sees himself as finished in his knowledge. Thus, assuming Continuing Education as necessary for a lifelong education and coming from a journey of studies aimed at the education of school teachers and realizing the scarcity of studies for the training process of Physical Education professionals not working in school, investigate whether the Continuing Education of Physical Education professionals at the gymnasiums in Cuiabá and Várzea Grande - MT happens, it occurs to us as a possibility to enter and understand these spaces more and, mainly, the training process of their professionals. Intentional non-probabilistic gyms in Cuiabá and Várzea Grande - MT were selected, in which the inclusion criterion adopted was that the gym should be a unit of some franchised gym network at the national and / or international franchised level, once that its repercussion and adhesion could be greater than other non-franchised academies. It was possible to identify six gyms that are in line with the inclusion criteria. The first contact made was with the person in charge of the unit in order to present the research objectives and clarify the ethical procedures. From six units contacted, 5 gymnasiums accepted to participate. For the academies that agreed to participate in the study, the Research Authorization Declaration was handed over to the academy for those responsible to sign. All Physical Education professionals trained in the institution were able to participate in this research, regardless of the position or function performed in the unit. Adding the 5 gyms, a total of 39 active Physical Education professionals were surveyed, of which 27 accepted to participate in the research. Through the responses it was possible to raise the adherence to online and face-to-face specialization courses as strategies for staying in the academies, as well as the financial progression in their professional performance. In other responses the presence of the desire for professional qualification to help students achieve a better self-esteem and self-image also appears. It is apprehended that the continuing education of these professionals has occurred, however, in a timid way from their responses. However, there is a need for the concepts to be guiding studies that permeate the universe of Continuing Education for professionals working in the Gymnasiums, to be increasingly guided by the reality of these spaces, distancing themselves from excessive conceptual approaches that were established for the school environment, but which can still echo in spaces other than these.